2019
DOI: 10.5812/ircmj.83614
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief in the Sickle-Cell Crisis: Intravenous Morphine Versus Ketorolac; A Double-Blind, Randomized Clinical Trial

Abstract: Background: Sickle cell disease (SCD) is a congenital hemoglobinopathy. A low Hb level and high hemoglobin-to-hematocrit ratio may lead to the vaso-occlusive crisis in patients, for the management of which hyperbaric oxygen, hydration, and pain relief therapy are proposed. Objectives: In this study, we sought to compare the effects of morphine and ketorolac on relieving painful sickle cell crisis. Methods: In this double-blind, randomized clinical trial, we recruited 92 SCD patients who referred to the Emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The results of another study demonstrated the better analgesic effects of intravenous ketorolac than nebulized fentanyl in patients with renal colic pain ( 22 ). The evidence indicated that injectable ketorolac and morphine produced almost the same analgesic effects in patients with sickle cell disease; nevertheless, ketorolac caused fewer complications ( 23 ). However, Tirupathi et al conducted a review study and concluded that further clinical trials were needed to prove the effectiveness of ketorolac in pain control ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of another study demonstrated the better analgesic effects of intravenous ketorolac than nebulized fentanyl in patients with renal colic pain ( 22 ). The evidence indicated that injectable ketorolac and morphine produced almost the same analgesic effects in patients with sickle cell disease; nevertheless, ketorolac caused fewer complications ( 23 ). However, Tirupathi et al conducted a review study and concluded that further clinical trials were needed to prove the effectiveness of ketorolac in pain control ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…21 Non-steroidal anti-inflammatory drugs are safer than opioids, with fewer side effects and the same pain-controlling effects. 22 In a qualitative study, many participants expressed their displeasure at being exposed to intravenous opioids at a young age, leading to increased hospitalisations in adulthood and dependence on opioids. 23 Therefore, raising patients' awareness of alternative methods and opioids' adverse effects should not be neglected as this could contribute to limiting frequent use of morphine.…”
mentioning
confidence: 99%